2014
DOI: 10.3747/co.21.1711
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Preoperative Serum Carcinoembryonic Antigen and Carbohydrate Antigen 19-9 in Colorectal Cancer

Abstract: Background: Since the first introduction of tumour markers, their usefulness for diagnosis has been a challenging question. The aim of the present prospective study was to investigate, in colorectal cancer patients, the relationship between preoperative tumour marker concentrations and various clinical variables. Methods: The study prospectively enrolled 131 consecutive patients with a confirmed diagnosis of colorectal carcinoma and 131 age- and sex-matched control subjects with no malignancy. The relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 32 publications
(29 reference statements)
4
31
1
1
Order By: Relevance
“…However, due to its limited sensitivity especially for early stage cancer, and its limited organ specificity, CEA is not regarded as suited as an individual diagnostic marker despite its undisputed value for monitoring tumor recurrence (35,36) and metastasis (37,38). In our analyses, CEA was found to have higher plasma levels in colorectal cancer patients at advanced stages compared with early ones, which is consistent with previous evidence (39).…”
Section: Discussionsupporting
confidence: 81%
“…However, due to its limited sensitivity especially for early stage cancer, and its limited organ specificity, CEA is not regarded as suited as an individual diagnostic marker despite its undisputed value for monitoring tumor recurrence (35,36) and metastasis (37,38). In our analyses, CEA was found to have higher plasma levels in colorectal cancer patients at advanced stages compared with early ones, which is consistent with previous evidence (39).…”
Section: Discussionsupporting
confidence: 81%
“…A study of CEA associated with malignancy reported that CEA level is positively correlated with tumor progression, with CEA positivity >50% in patients with tumor lymph node metastasis . Additionally, serum CEA level in patients with colorectal cancer was significantly higher than that in a noncancerous group, and CEA concentrations in phase III and phase IV were significantly higher than those detected in phase I. Colorectal cancer patients with lymph node metastases or distant metastases showed significantly increased serum CEA concentrations relative to controls and early‐stage patients . The present study found that salivary CEA levels in OSCC patients were correlated with clinical stage and lymph node metastasis, whereas serum CEA level was correlated with lymph node metastasis.…”
Section: Discussionsupporting
confidence: 52%
“…28 Additionally, serum CEA level in patients with colorectal cancer was significantly higher than that in a noncancerous group, and CEA concentrations in phase III and phase IV were significantly higher than those detected in phase I. Colorectal cancer patients with lymph node metastases or distant metastases showed significantly increased serum CEA concentrations relative to controls and earlystage patients. 29 The present study found that salivary CEA levels in OSCC patients were correlated with clinical stage and lymph node metastasis, whereas serum CEA level was correlated with lymph node metastasis. Our results confirmed that salivary CEA can be used as an indicator of OSCC severity and served as a method of assessing OSCC staging and lymph node invasion.…”
Section: Discussionmentioning
confidence: 44%
“…The key point of these observations is that the threshold values of both markers for occult unresectable esophageal World J Surg cancer were much lower (more or less half of them) than those reported as common ''normal'' values (usually calculated on pancreatic cancer patients) [15]. This data should be carefully taken in consideration when a final preoperative evaluation is carried on.…”
Section: Discussionmentioning
confidence: 96%